Pendapatan Usaha Penetasan Telur Itik Skala Kecil di Kabupaten Jember : Income of Small-Scale Duck Egg Hatchery Enterprises in Jember Regency - Subagja, Hariadi; Kustiawan, Erfan; Hasanah, Niswatin; Laksito Rukmi, Dyah; Supriadi Saleh, Anang (Jurnal Ilmiah Inovasi, 2025)
This study aims to analyze the income efficiency level of small-scale duck egg hatching businesses with an incubator capacity of 1,000 eggs in Jember Regency in 2025. The analysis focuses on financial aspects, including production costs, revenue, income, profitability, the revenue-cost ratio (R/C ratio), and the Break-Even Point (BEP). Data were collected through field observations and direct interviews with hatchery farmers in Jember, East Java. The results showed that the average production cost per period was IDR 5,500,000 with a total revenue of IDR 5,600,000, resulting in a net income of IDR 100,000 per period. The BEP value was 786 units with a BEP price of IDR 6,875 per duckling, while the R/C ratio was 1.02 and profitability was 1.82%. Although the profit margin is relatively low, duck egg hatching businesses in Jember remain feasible to operate with improved management efficiency, particularly in feed cost control and hatchability optimization.